2021
DOI: 10.3390/membranes11030200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Anthocyanins and Their Fouling Mechanisms during Non-Thermal Nanofiltration of Blueberry Aqueous Extracts

Abstract: Organic fouling in the nanofiltration (NF) process, which is a non-thermal technology to recover active components, is a critical problem limiting its applications. This study seeks to identify the anthocyanins on the NF membrane and explore their fouling mechanisms during concentration of blueberry extracts. Seven kinds of monomeric anthocyanins in foulants—delphinidin-3-O-galactoside, delphinidin-3-O-glucoside, delphinidin-3-O-arabinoside, cyanidin-3-O-galactoside, petunidin-3-O-galactoside, peonidin-3-O-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Since the cake layer contributed to the separation, the presence of a reversibly adsorptive layer on the membrane surface also results in the higher rejection of benzoic acid in fresh cranberry juice than in UF-treated juice because the cake layer contributed to the separation. The reversibly adsorptive layer is constituted by interaction between high-molecular-weight compounds, such as anthocyanin and membrane material, which is attributed to molecular interactions, such as hydrophobic interactions and hydrogen bonds [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the cake layer contributed to the separation, the presence of a reversibly adsorptive layer on the membrane surface also results in the higher rejection of benzoic acid in fresh cranberry juice than in UF-treated juice because the cake layer contributed to the separation. The reversibly adsorptive layer is constituted by interaction between high-molecular-weight compounds, such as anthocyanin and membrane material, which is attributed to molecular interactions, such as hydrophobic interactions and hydrogen bonds [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…It would have been majorly formed by phenolics and probably by some anthocyanins present in the Muérdago fruit [1]. Fouling layers formed by these compounds have been observed during the nanofiltration of blueberry aqueous extracts (anthocyanin fouling) [19], the nanofiltration of model juice solutions (phenolics) [20], among others. Means within columns and rows followed by different letters are significantly different (p < 0.0500).…”
Section: Visual Membrane Inspection and Characterizationmentioning
confidence: 99%
“…In 2021, Li et al reported a study to assess the efficiency of extraction methods from conventional (solvent and ultrasonic extraction) to enzymatic extraction for anthocyanins and their antioxidant properties following each extraction method [ 134 ]. Several reports [ 83 , 97 , 102 , 104 , 106 , 108 , 109 , 110 , 111 , 112 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ] observed that the quantity of anthocyanins in blueberries varies based on the place, collecting/harvesting season, extraction solvent, extraction method, and method of analysis.…”
Section: Analytical Techniques Including Identification and Quantific...mentioning
confidence: 99%